Foamed light soil and preparation method thereof

The preparation of foam light soil by combining the pyrolysis residues of air-accumulated sand and oil sludge and foaming is solved, and the problems of poor water permeability and low shear strength of air-accumulated sand in roadbed filling are achieved, and efficient roadbed materials are achieved The preparation meets the strength requirements of the roadbed, promotes the utilization of resources, and reduces environmental pollution and engineering costs.

CN119263744APending Publication Date: 2025-01-07XINJIANG TRANSPORTATION PLANNING SURVEYING & DESIGN INST
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411699660.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The problem of poor water permeability and poor water retention in roadbed filling is that it is difficult to directly apply to roadbed filling in natural state, and its engineering properties are poor, low shear strength, easy to loosen and displace. The mechanical properties of foamed soil also need to be improved.

Method used

The foam group is made by combining the pyrolytic residue of air-accumulated sand with oil sludge with cement, and mixing the foaming agent with water to form a foam light soil with good fluidity and mechanical properties.

Benefits of technology

The prepared foam light soil has high compressive strength, flexural strength and low density, which meets the requirements of roadbeds of different layers and grades, and has no heavy metal leaching, which has no impact on the environment, solving the problem of wind-stacked sand and oil sludge heat. Resolve the problem of residue accumulation, realize the coordinated utilization of resources, and reduce project costs and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides foamed light soil. The foamed light soil is prepared from the following raw materials in percentage by mass: 0.01%-30.00% of aeolian sand, 0.01%-30.00% of oily sludge pyrolysis residues, 25.00%-76.00% of cement, 3.00%-5.00% of a foam group and 20.00%-25.00% of water, wherein the foam group is prepared by mixing a foaming agent with water and then foaming. The invention provides a preparation method of foamed light soil. The foamed light soil prepared by compounding the aeolian sand and the oily sludge pyrolysis residues with the cement has good fluidity and mechanical properties, such as high compressive strength, high breaking strength, no heavy metal leaching, no influence on the environment and the like, meets the requirements of different layers and different grades of highway subgrades, and has good application prospects. And the regulation of foam light soil on the roadbed strength is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to foamed lightweight soil and a preparation method thereof. Background Art

[0002] Foamed concrete is a porous concrete made by physically making foam from a foaming agent aqueous solution, then adding the foam to a slurry made of cement, aggregate, admixture, additive and water, and then mixing, pouring, and naturally or steam curing. It contains a large number of closed pores, and exhibits good physical and mechanical properties and functions, such as light weight, heat preservation, heat insulation, moisture resistance, sound insulation, and water avoidance. Foamed concrete is mainly used in wall and roof insulation projects, lightweight concrete components and products, building floor heating systems, large tunnels, high-grade highways and subway backfill projects, building lightweight cushions, sound absorption and insulation barriers, etc.

[0003] Aeolian sand is fine particles with a medium particle size of less than 0.15 mm formed by wind erosion, transportation, and accumulation. Aeolian sand has poor engineering properties. In its natural state, the cohesion of aeolian sand is almost zero, and its shear strength is low. It is easy to loosen and move under the action of external forces. At the same time, aeolian sand has good water permeability and poor water retention. Even if a large amount of water is added to the sand, the water content of the upper layer will be low due to the rapid infiltration of water. Therefore, it is difficult to directly use aeolian sand for roadbed filling. The prior art discloses that aeolian sand and cement are prepared into foamed soil under the action of a foaming agent, which has the effects of heat preservation, heat insulation and load reduction, but the mechanical properties of the foamed soil need to be improved. Summary of the invention

[0004] In view of this, the present invention provides a foamed lightweight soil and a preparation method thereof. The foamed lightweight soil provided in the present application has good fluidity and mechanical properties.

[0005] The present application provides a foamed lightweight soil, which is made of the following raw materials in percentage by weight: 0.01% to 30.00% of aeolian sand, 0.01% to 30.00% of oil sludge pyrolysis residue, 25.00% to 76.00% of cement, 3.00% to 5.00% of foam group and 20.00% to 25.00% of water;

[0006] The foam group is prepared by mixing a foaming agent with water and then foaming.

[0007] The foamed lightweight soil prepared by compounding aeolian sand and oil sludge pyrolysis residue with cement has good fluidity and mechanical properties.

[0008] This application uses aeolian sand as raw material. Aeolian sand is fine particles formed by wind erosion, transportation, and accumulation. This application has five special restrictions on its source. In some specific implementations, the median particle size of the aeolian sand is less than 0.15 mm, preferably less than 0.10 mm. In some specific implementations, the mass percentage of the aeolian sand in the total raw materials is 0.01% to 30.00%, preferably 0.05% to 25.01%, more preferably 5% to 25%, and most preferably 10% to 25%.

[0009] The present application uses oil sludge pyrolysis residue as raw material, and the oil sludge pyrolysis residue is a solid waste formed by the adhesion and penetration of petroleum substances during the process of oil extraction, refining, storage, and use, and is the product after abrasion treatment. The present application has no special restrictions on the source of the oil sludge pyrolysis residue, and it can be prepared according to the following method:

[0010] The oily sludge pyrolysis residue is subjected to abrasion treatment and sieved to obtain the product.

[0011] The present application has no particular restrictions on the source of the oily sludge pyrolysis residue, which can be purchased from the market or prepared by heat-treating oily sludge solid waste. After obtaining the oily sludge pyrolysis residue, it is subjected to abrasion treatment, preferably using an MH-II Los Angeles abrasion tester for 400 to 600 cycles, preferably 500 cycles, and then sieved to obtain the oily sludge.

[0012] In some specific implementations, the median particle size of the oil sludge pyrolysis residue is less than 0.25 mm, preferably less than 0.050 mm. In some specific implementations, the mass percentage of the oil sludge pyrolysis residue in the total raw material is 0.01% to 30.00%, preferably 0.05% to 26.23%, more preferably 5% to 26%, and most preferably 10% to 25%.

[0013] In some specific implementations, the mass ratio of the aeolian sand to the oil sludge pyrolysis residue is 60-150:60-150, preferably 60-120:60-150.

[0014] The present application uses cement as a raw material, and the present application has no special restrictions on the cement, preferably a silicate cement with a PM42.5 or higher, and more preferably a PM42.5 silicate cement. In some specific implementations, the mass percentage of the cement in the total raw materials is 25.00% to 76.00%, preferably 26.08% to 75.08%, more preferably 27% to 75%, and most preferably 30% to 65%.

[0015] The present application uses a foam group as a raw material, and the foam group is a product obtained by mixing a foaming agent with water and foaming. The present application has no special restrictions on the foaming agent, including but not limited to HT composite foaming agent, resin foaming agent, AOS foaming agent, etc., preferably HT composite foaming agent. The present application has no special restrictions on the source of the foam group, and it is preferably prepared according to the following method:

[0016] The foaming agent and water required to dilute the foaming agent 35 to 55 times are mixed evenly and then foamed to obtain a foam group.

[0017] In some specific implementations, the present application preferably uses a foaming agent for foaming. During foaming, the rotation speed of the foaming agent is preferably 300 rpm to 500 rpm, more preferably 350 rpm to 450 rpm, and most preferably 430 rpm.

[0018] In some specific implementations, the water is preferably distilled water. When the foaming agent is a HT composite foaming agent, the water temperature of the water is preferably 20°C ± 2°C.

[0019] In some specific implementations, the mass ratio of the foaming agent to water is 1:40 to 50, preferably 1:40 to 48, and more preferably 1:40 to 45. In some specific implementations, the mass percentage of the foam group to the total raw materials is 3.00% to 5.00%, preferably 3.01% to 4.64%.

[0020] The raw materials described in the present application also include water, and the water is preferably distilled water. The mass percentage of the water in the total raw materials is 20.00% to 25.00%, preferably 21.46% to 24.06%.

[0021] In some specific implementations, the water-to-solid ratio in the raw material is 0.29: 1 to 0.33: 1, preferably 0.32 to 0.33: 1. In some specific implementations, the volume ratio of the foam to the slurry is 0.8: 1 to 1.2: 1.

[0022] The present application provides a method for preparing the foamed lightweight soil described in the above technical solution, comprising the following steps:

[0023] a) Evenly mix aeolian sand, oil sludge pyrolysis residue, cement and water;

[0024] b) The mixture obtained in step a) is mixed evenly with the foam group, and the foamed lightweight soil is obtained after molding.

[0025] The present application first mixes aeolian sand, oil sludge pyrolysis residue, cement and water evenly. The present application preferably mixes aeolian sand, oil sludge pyrolysis residue, cement and water evenly in an SJ-15 mortar mixer. In some specific implementations, the mixing time is 80s~120s, and the mixing speed is 50 rpm~100 rpm, preferably 80±4 rpm.

[0026] After the mixture is obtained, it is mixed with the foam group, preferably stirred and mixed evenly in a mortar mixer to obtain a slurry. In some specific implementations, the stirring and mixing time is 80s to 120s, and the stirring and mixing speed is 50 rpm to 100 rpm, preferably 80±4 rpm.

[0027] After obtaining the slurry, it is subjected to molding treatment to obtain foamed lightweight soil. Specifically, the present application first applies vaseline to the mold, then pours the slurry into the mold, scrapes it flat, covers it with plastic wrap, and then allows the slurry to stand to form, and then demolds to obtain the foamed lightweight soil.

[0028] The present application also provides a roadbed material, comprising the foam lightweight soil described in the above technical solution.

[0029] The foamed lightweight soil prepared by compounding aeolian sand and oil sludge pyrolysis residue with cement has good fluidity and mechanical properties, such as high compressive strength, high flexural strength, no heavy metal leaching, no impact on the environment, etc., meets the requirements of roadbeds of highways at different levels and different grades, and meets the requirements of foamed lightweight soil on roadbed strength. The compressive strength of the foamed lightweight soil with aeolian sand and oil sludge pyrolysis residue of the present invention can reach up to 4.21MPa after 28 days of curing, and no harmful substances are leached; compared with ordinary silicate cement, the foamed lightweight soil with aeolian sand and oil sludge pyrolysis residue of the present invention has a low density, and the production of the same volume of foamed lightweight soil is 1 / 3 to 1 / 6 of the mass of cement. In addition, the present invention converts aeolian sand and solid waste oil sludge pyrolysis residues into building materials, avoiding environmental pollution and land resource occupation caused by the accumulation of aeolian sand and oil sludge pyrolysis residues, greatly increasing the demand for aeolian sand and oil sludge pyrolysis residues in the project, realizing the coordinated utilization of aeolian sand and oil sludge pyrolysis residues, improving the resource utilization efficiency of idle resources aeolian sand and oil sludge pyrolysis residues, alleviating the tense situation of shortage of road gravel and fill materials, achieving the purpose of saving resources and reducing engineering costs, and having significant economic and social environmental benefits. The experimental results show that the present application significantly enhances the fluidity, flexural strength and 20-day compressive strength of the obtained foamed lightweight soil by compounding aeolian sand and oil sludge pyrolysis residues. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1A schematic diagram of the process for preparing the foamed lightweight soil provided in this application;

[0031] Figure 2 The loading method for the flexural strength test provided in the embodiment of the present application;

[0032] Figure 3 This is a microscopic electron microscope photograph of the foamed lightweight soil prepared in the example of the present application. DETAILED DESCRIPTION

[0033] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.

[0034] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.

[0035] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.

[0036] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the invention and does not limit the scope of the invention unless otherwise claimed. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the invention.

[0037] In addition, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values ​​in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values ​​and percentages used in this disclosure are modified by "about". Here, "about" generally means that the actual value is within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.

[0038] The present application provides a method for preparing foamed lightweight soil, comprising the following steps:

[0039] a) Evenly mix aeolian sand, oil sludge pyrolysis residue, cement and water;

[0040] b) The mixture obtained in step a) is mixed evenly with the foam group, and the foamed lightweight soil is obtained after molding.

[0041] See also Figure 1 , Figure 1 The present application provides a flow chart of the method for preparing foamed lightweight soil, wherein cement, aeolian sand, oil sludge pyrolysis residue and water are uniformly mixed in a mortar mixer to obtain a slurry; a foaming agent and water are uniformly mixed and foamed by a foaming machine to obtain a foam group; the obtained slurry and the foam group are mixed to obtain a foamed lightweight soil slurry, and the foamed lightweight soil can be obtained after molding.

[0042] The foamed lightweight soil prepared by compounding aeolian sand and oil sludge pyrolysis residue with cement has good fluidity and mechanical properties.

[0043] The foamed lightweight soil and its preparation method provided by the present application are further described below in conjunction with embodiments.

[0044] Through variance analysis, in this application, the main factors affecting the compressive strength of foam lightweight soil are the volume ratio of foam to slurry and the water-solid ratio, the main factor affecting the flexural strength of foam lightweight soil is the volume ratio of foam to slurry, and the main factor affecting the fluidity of foam lightweight soil is the water-solid ratio. Therefore, the following embodiments are provided based on the above influencing factors.

[0045] In the following embodiments, aeolian sand refers to fine particles with a medium particle size of less than 0.15 mm formed by wind erosion, transportation, and accumulation;

[0046] The oily sludge pyrolysis residue was prepared according to the following method: the oily sludge pyrolysis residue solid waste purchased from the market was abraded for 500 cycles by a MH-II Los Angeles abrasion tester and then passed through a 0.3 mm sieve;

[0047] The cement is PM42.5 silicate cement.

[0048] Example 1

[0049] (1) Preparation of foaming agent: Measure the HT composite foaming agent. When measuring the foaming agent, if there is foam in it, let it stand for a while, wait for it to disappear before reading, and dilute it with 20±2℃ water according to a 45-fold dilution factor. It is worth noting that after pouring the foaming liquid in the measuring cylinder into the small bucket, the measuring cylinder should be rinsed 2 to 3 times and then the liquid should be poured into the configured small bucket. After stirring for 60 seconds, wait until the liquid is fully mixed and then use the HT-20 foaming machine to foam at a speed of 430 rpm. The foaming process is controlled according to the predetermined volume ratio of foam and slurry to obtain a foam group of predetermined volume.

[0050] (2) Weighing: According to the mass percentages of aeolian sand, oil sludge pyrolysis residue, cement, foam group and distilled water being 16.90%, 12.67%, 43.33%, 3.04% and 24.06% respectively, i.e. the water-solid ratio being 0.33:1, and according to the volume ratio of foam to slurry being 0.8:1, prepare the foam group of corresponding volume, and weigh 120 g of aeolian sand, 90 g of oil sludge pyrolysis residue, 307.6 g of cement, 21.6 g of foam group and 170.8 g of distilled water respectively.

[0051] (3) Prepare foamed lightweight soil slurry: Pour the weighed aeolian sand, oil sludge pyrolysis residue, cement and water into a mortar mixer. The amount to be mixed at one time is the amount of 5 to 6 100*100*100 mm molds. Turn on the switch and stir for 90 seconds until the aeolian sand, oil sludge pyrolysis residue and cement are evenly mixed. Then pour the foam group evenly into the mortar mixer. Turn on the switch and stir quickly for 90 seconds until the aeolian sand and oil sludge pyrolysis residue are fully mixed to obtain foamed lightweight soil.

[0052] (4) Molding and curing: Clean the inside and surface of the triple mold in advance to ensure that there is no dirt, then evenly smear the inner wall with vaseline, pour the obtained foam lightweight soil slurry of aeolian sand, oil sludge pyrolysis residue into the triple mold, ensure that the slurry is filled in the corners, then use a scraper to flatten the surface and cover it with plastic wrap. After the foam lightweight soil is formed, let it stand at room temperature for 24 hours, use an air pump to demold it, and finally put the specimen into a standard curing room with a temperature of 25±2℃ and a humidity of ≥95%, and cure it for 3d, 7d, and 28d respectively to the corresponding age.

[0053] The fluidity, wet density, unconfined compressive strength at 3d, 7d and 28d, flexural strength and heavy metal leaching characteristics were tested respectively. The test results are shown in Table 1. Table 1 is the performance test results of the foamed lightweight soil prepared in the embodiments and comparative examples of the present application.

[0054] The test methods and test conditions for each item are as follows:

[0055] (a) Fluidity

[0056] In this test, fluidity is used to characterize the pouring characteristics of the foamed lightweight soil roadbed of aeolian sand, oil sludge and pyrolysis residue. The test conditions are controlled as follows: the steel barrel has a diameter of 10 cm and a height of 10 cm. The foamed lightweight soil slurry fills the steel barrel and is scraped flat and left to stand for 60 seconds to achieve a fluidity control range of 160~190 mm.

[0057] (b) Wet density

[0058] This test uses wet density to characterize the quality characteristics of aeolian sand, oil sludge, pyrolysis residue, foamed lightweight soil roadbed. The test conditions are as follows: measure the volume of the filled measuring cup, measure 3 times and take the average value, and the wet density range should be 500~1100kg / m 3 .

[0059] (c) 28d unconfined compressive strength

[0060] This test uses the 28d unconfined compressive strength to characterize the strength characteristics of the aeolian sand, oil sludge, pyrolysis residue, foamed lightweight soil roadbed. The test conditions are controlled as follows: the size of the specimen is to cure the formed specimen at a temperature of 25℃±2℃ and humidity>95% to 3d, 7d, and 28d, and use a hydraulic press to perform a compression test on the specimen at a loading rate of 2kn / s.

[0061] d) Flexural strength

[0062] Place the test piece with a length*width*height of 100mm*100mm*400mm on the bending support roller, with the support point spacing of 300mm. Start the test machine. When the pressure roller approaches the test piece, adjust the pressure roller and the support roller to make the contact balanced. The dimensional deviation of all spacings should not be greater than ±1mm. Figure 2 As shown, Figure 2 This is a loading method for the flexural strength test provided in the embodiments of the present application.

[0063] The foamed lightweight soil prepared in Example 1 was subjected to microscopic electron microscope analysis. The results are shown in Figure 3 , Figure 3 This is a microscopic electron microscope photo of the foamed lightweight soil prepared in the embodiment of this application. Figure 3 It is known that the foamed lightweight soil sample prepared in the present application has a small and uniform foam diameter inside, forming a thicker pore wall without the existence of through holes. At the same time, the flocculent structure of hydrated calcium silicate consolidates the aeolian sand and the pyrolysis residue of the oil sludge, which helps to form a stable structure between the foams.

[0064] Example 2

[0065] The difference from Example 1 is that the doping amount of oil sludge pyrolysis residue is 150g, the doping amount of aeolian sand is 90g, the volume ratio of foam to slurry is 0.9:1, the dilution multiple of the foaming agent is 35, the stirring time is 110s, and the water-solid ratio is the same as that in Example 1. The test results are shown in Table 1, which shows the performance test results of the foamed lightweight soil prepared in the examples and comparative examples of the present application.

[0066] Comparative Example 1

[0067] The difference from Example 1 is that the doping amount of oil sludge pyrolysis residue is 0g, the doping amount of aeolian sand is 150g, the volume ratio of foam to slurry is 1.2:1, the dilution multiple of the foaming agent is 55, the stirring time is 120s, and the water-solid ratio is the same, both 0.33:1. The test results are shown in Table 1, which shows the performance test results of the foamed lightweight soil prepared in the embodiments of the present application and the comparative examples.

[0068] Comparative Example 2

[0069] The difference from Example 1 is that the doping amount of oil sludge pyrolysis residue is 120g, the doping amount of aeolian sand is 0g, the volume ratio of foam to slurry is 0.9:1, the dilution multiple of the foaming agent is 40, and the stirring time is 100s. The test results are shown in Table 1, which shows the performance test results of the foamed lightweight soil prepared in the embodiments of the present application and the comparative examples.

[0070] Comparative Example 3

[0071] The difference from Example 1 is that the doping amount of oil sludge pyrolysis residue is 150g, the doping amount of aeolian sand is 0g, the water-solid ratio is 0.31:1, the volume ratio of foam to slurry is 1.2:1, the dilution multiple of the foaming agent is 50, and the stirring time is 90s, the same as in Example 1. The test results are shown in Table 1, which shows the performance test results of the foamed lightweight soil prepared in the embodiments of the present application and the comparative examples.

[0072] Example 3

[0073] The difference from Example 1 is that the doping amount of oil sludge pyrolysis residue is 60g, the doping amount of aeolian sand is 120g, the water-solid ratio is 0.30:1, the volume ratio of foam to slurry is 1.2:1, the dilution multiple of the foaming agent is 35, and the stirring time is 100s. The test results are shown in Table 1, which shows the performance test results of the foamed lightweight soil prepared in the embodiments of the present application and the comparative examples.

[0074] Example 4

[0075] The difference from Example 1 is that the doping amount of oil sludge pyrolysis residue is 90g, the doping amount of aeolian sand is 90g, the water-solid ratio is 0.32:1, the volume ratio of foam to slurry is 1.2:1, the dilution multiple of the foaming agent is 40, and the stirring time is 80s. The test results are shown in Table 1, which shows the performance test results of the foamed lightweight soil prepared in the embodiments of the present application and the comparative examples.

[0076] Example 5

[0077] The difference from Example 1 is that the doping amount of oil sludge pyrolysis residue is 120g, the doping amount of aeolian sand is 60g, the water-solid ratio is 0.29:1, the volume ratio of foam to slurry is 1.2:1, the stirring time is 110s, and the dilution factor of the foaming agent is 45, which is the same as that in Example 1. The test results are shown in Table 1, which shows the performance test results of the foamed lightweight soil prepared in the examples and comparative examples of the present application.

[0078] Table 1 Performance test results of foamed lightweight soil provided in Example 1 of this application

[0079]

[0080] As can be seen from Table 1, the present application compounds aeolian sand and oil sludge pyrolysis residue with cement to prepare foamed lightweight soil, which greatly improves its fluidity, compressive strength and flexural strength.

[0081] Specifically, the fluidity of the foamed lightweight soil prepared by the pyrolysis residue of aeolian sand and oil sludge in this application is 160~190mm, which complies with the fluidity "Technical Code for Design and Construction of Cast-in-Place Foam Lightweight Soil Roadbed" (TJGF1001-2011) and "Technical Code for Bubble Mixed Lightweight Soil Filling Engineering" (CJJ177-2012-T).

[0082] The 28d compressive strength of the foamed lightweight soil of pyrolysis residue of aeolian sand and oil sludge prepared in this application is greater than 0.4MPa, which meets the roadbed filling conditions in the "Technical Code for Bubble Mixed Lightweight Soil Filling Engineering" (CJJ177-2012-T).

[0083] It can be seen from Example 1, Example 2, Comparative Example 1 and Comparative Example 2 that the pyrolysis residues of aeolian sand and oil sludge enhance the fluidity of the prepared foamed lightweight soil.

[0084] It can be seen from Example 3, Example 4, Example 5, Comparative Example 1 and Comparative Example 3 that the compounding of aeolian sand and oil sludge pyrolysis residue enhances the flexural strength of the prepared foamed lightweight soil.

[0085] It can be seen from Example 1, Example 4, Example 5, Comparative Example 1 and Comparative Example 3 that the compounding of aeolian sand and oil sludge pyrolysis residue improves the 28d compressive strength of the prepared foamed lightweight soil.

[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A foamed lightweight soil, made from the following raw materials in percentage by weight: 0.01% to 30.00% of aeolian sand, 0.01% to 30.00% of oil sludge pyrolysis residue, 25.00% to 76.00% of cement, 3.00% to 5.00% of foam group and 20.00% to 25.00% of water; in, The foam group is prepared by mixing a foaming agent with water and then foaming.

2. The foamed lightweight soil according to claim 1, characterized in that: The mass ratio of the aeolian sand to the oil sludge pyrolysis residue is 60-150:60-150.

3. The foamed lightweight soil according to claim 2, characterized in that: In the raw materials, the water-to-solid ratio is 0.29:1-0.33:1, and the volume ratio of foam to slurry is 0.8:1-1.2:

1.

4. The foamed lightweight soil according to any one of claims 1 to 3, characterized in that: The foaming agent is a HT composite foaming agent, a resin foaming agent or an AOS foaming agent; The mass ratio of the foaming agent to water is 1:40-50.

5. The foamed lightweight soil according to claim 4, characterized in that: The median particle size of the aeolian sand is less than 0.15 mm; The median particle size of the oil sludge pyrolysis residue is less than 0.25 mm.

6. The foamed lightweight soil according to claim 5, characterized in that: The oil sludge pyrolysis residue is prepared according to the following method: The oily sludge pyrolysis residue is subjected to abrasion treatment and sieved to obtain the product.

7. The foamed lightweight soil according to claim 4, characterized in that: The cement is silicate cement with a PM of more than 2.

5.

8. The method for preparing the foamed lightweight soil according to any one of claims 1 to 7, comprising the following steps: a) Evenly mix aeolian sand, oil sludge pyrolysis residue, cement and water; b) The mixture obtained in step a) is mixed evenly with the foam group, and the foamed lightweight soil is obtained after molding.

9. The preparation method according to claim 8, characterized in that: In step a), the mixing time is 80s to 120s; In step b), the mixing time is 80s to 120s.

10. A roadbed material, characterized in that: The invention comprises the foamed lightweight soil as described in any one of claims 1 to 7.

Citation Information

Cited By

  • Light energy-saving fireproof soil-based foam light soil and preparation method thereof

    CN120483662A

  • Lightweight energy-saving fireproof soil base foam lightweight soil and preparation method thereof

    CN120483662B